Base Account as Safe Spaces: A Virtual Ethnographic Study of Boys Love Fans Interactions on the X Account @fessthaii - Kanaya Mulia Putri; Filosa Gita Sukmono (Universitas Ahmad Dahlan, 2026)
This study examines how the Twitter/X base account @fessthaii functions as a safe space for Thai Boys Love (BL) fans in Indonesia, where BL consumption often encounters stigma within a heteronormative social context. While anonymity on digital platforms is commonly assumed to create safe spaces, limited research has explored how safety is socially constructed within anonymous fandom communities. This research adopts a constructivist paradigm and employs virtual ethnography. Data were collected through participant observation, online interviews with five active followers, and documentation of menfess posts, comment threads, and moderation practices. Data were analyzed using Analisis Media Siber (AMS) across four levels: media space, media document, media object, and media experience. The findings show that @fessthaii operates as a safe space not merely through anonymity but through continuous social negotiation involving moderation practices, community rules, peer support, and affective labour from administrators. Safety is therefore produced relationally through interaction, shared norms, and power relations rather than as a technical feature of the platform. This study contributes to digital media and fandom studies by demonstrating that safe spaces in stigmatized online communities are actively constructed through governance and collective participation.